2021
DOI: 10.1002/ece3.7799
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling biotic and abiotic drivers of intraspecific trait variation in woody plant seedlings at forest edges

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 65 publications
0
1
0
Order By: Relevance
“…Also, consideration of environmental factors is of great importance in understanding the state, stability, and ecological role of forest stands [56][57][58][59][60][61][62][63]. It is especially important for protection and restoration of forest ecosystems [64][65][66] as well as in their management [67][68][69]. Accounting for the data obtained on the bioecological features of forest stands and environmental conditions are of paramount importance in managing the resource qualities of forest ecosystems, their stability and protection in forest-steppe and other landscapes.…”
Section: Discussionmentioning
confidence: 99%
“…Also, consideration of environmental factors is of great importance in understanding the state, stability, and ecological role of forest stands [56][57][58][59][60][61][62][63]. It is especially important for protection and restoration of forest ecosystems [64][65][66] as well as in their management [67][68][69]. Accounting for the data obtained on the bioecological features of forest stands and environmental conditions are of paramount importance in managing the resource qualities of forest ecosystems, their stability and protection in forest-steppe and other landscapes.…”
Section: Discussionmentioning
confidence: 99%
“…The final path model was refitted with z‐transformed variables in order to obtain the relative strength of each path (i.e., standardized regression coefficients). All data associated with this study can be found in Zheng et al (2023).…”
Section: Methodsmentioning
confidence: 99%